The impact of vaccination on patients with COVID-19 during the wave of Omicron in Shanghai - Yu, Chen; Fengzhao, Zhu; Hongmei, Wu; Zeyuan, Lei; Yu, Liu; Yuhang, Guo; Rufei, Shen; Qingzhu, Jia; Xiaorong, Sun; Xia, Wang; Caiping, Song; Zhi, Xu; et al. (Frontiers in Public Health, 2022)
Background The global health has been affected by the COVID-19 pandemic persistently, of which Omicron is currently the predominant variant. However, the impact of vaccination on Omicron remained uncertain. Objective This study sought to explore the effect of vaccination on patients infected with Omicron. Methods A retrospective observational cohort was conducted in the largest Fangcang shelter hospital in Shanghai from April 1 to May 30, 2022. The demographics, length of hospital stay, clinical symptoms, the comorbidities and vaccination status were recorded. Clinical outcomes of the vaccinated and non-vaccinated groups were compared and analyzed. Results Of the 3119 patients who fulfilled the eligibility criteria and were enrolled in the study, 2226 (71.4%) patients had received nCoV-19 vaccine while 893 (28.6%) patients had not received it before admission. Patients in the vaccinated group had significantly shorter length of hospital stay than those in the unvaccinated group (15.48 ± 2.708 vs. 15.85 ± 3.102, p＜0.001). More asymptomatic patients were observed in the vaccinated group than the non-vaccinated (70.4% vs. 64.5%, p＜0.001). Further subgroup analysis demonstrated that the older the age, the more significant the difference was (p＜0.005). Conclusions Vaccination was associated with a significant reduction in the severity of Omicron infection compared with no vaccination. Vaccination appears to make Omicron-infected people with milder symptoms than unvaccinated people. This suggests the potential effectiveness of current vaccines against Omicron.